The Impact of Education Policy on Equity of Access to Education in Indonesia and New Zealand - Fitri Noviani, Fitri Noviani; Yulensi Klareza; Dwi Fahmilia; Irwan Koto (TOFEDU: The Future of Education Journal, 2025)
Education is vital for national development, yet access disparities persist. This study compares education policies in Indonesia and New Zealand, analyzing their effectiveness in ensuring equity. Using a qualitative comparative method, data from government reports and academic sources were examined. Findings show Indonesia struggles with economic and geographic barriers despite programs like KIP and BOS, while New Zealand’s decentralized system and financial aid improve access, though ethnic gaps remain. Strong governance and targeted policies in New Zealand help reduce disparities, offering lessons for Indonesia to enhance infrastructure, teacher distribution, and digital access. Future research should explore socio-economic impacts and long-term outcomes.